Flight behavior : a novel - Kingsolver, Barbara (New York : Harper, 2012)
Tired of living on a failing farm and suffering oppressive poverty, bored housewife Dellarobia Turnbow, on the way to meet a potential lover, is detoured by a seemingly miraculous event on the Appalachian mountainside that ignites a media and religious firestorm that changes her life forever.
Keywords: Women biologists -- Fiction; Curiosities and wonders -- Fiction; Families -- Fiction; Tennessee -- Fiction; Suspense fiction